Uji Validitas Konstruk Pembentukan Karakter Moral Remaja - Layyinah, Layyinah; Roebianto, Adiyo (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2020)
Moral is an important thing in a person's character. However, today Indonesian society has experienced many moral setbacks, especially among adolescents. This causes a moral crisis in adolescents. Although the crisis was realized, it was never known empirically about the moral crisis that occurred. This study intends to test the construct validity of the moral character instrument by means of a confirmatory factor analysis approach. The author's moral character instrument is compiled using a Likert model. Participants in this study were junior high and high school students in two different schools with a total of 153 (n = 153). The results of the CFA analysis show that the multidimensional model on moral instruments is declared fit with the data. However, there are several notes regarding the considerable number of invalid statement items on moral instruments.